2009
DOI: 10.1590/s0100-879x2009005000004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood neoangiogenesis and lymphatic vascularization in colorectal adenomas from patients with and without concomitant colorectal cancer

Abstract: Blood and lymphatic vessel proliferation is essential for tumor growth and progression. Most colorectal carcinomas develop from adenomas (adenoma-carcinoma sequence) in a process due to accumulation of molecular genetic alterations. About 5% of adenomatous polyps are expected to become malignant, but data on the differential angiogenic patterns of these lesions in patients with and without concomitant cancer are missing. The aim of the present study is to compare the angiogenic and lymphatic patterns of adenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…determined MVD and total vascular area by computer image analysis and reported that there was no significant difference of MVD or total vascular area counts among histologic types of adenoma (tubular, tubulovillous, and villous) in agreement with the present work. [30]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…determined MVD and total vascular area by computer image analysis and reported that there was no significant difference of MVD or total vascular area counts among histologic types of adenoma (tubular, tubulovillous, and villous) in agreement with the present work. [30]…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the endothelial area was made only when endothelial wall was identified by brown stain. [233038]…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Moreia et al23 performed a retrospective study including 10 colorectal non-neoplastic lesions, 30 colorectal adenomas and 60 sporadic CRC tumors and found that LMVD increased significantly and sequentially from non-neoplastic tissues to adenomas and cancerous tumors. Another study showed that LMVD was significantly higher in adenomas from patients with carcinoma than those in patients without cancer 24. However, Liang et al11 reported that LMVD was not higher in colorectal adenomas than in normal colorectal tissues and that LMVD was significantly higher in T1 carcinomas than in Tis carcinomas, colorectal adenomas and normal tissues.…”
Section: Lymphangiogenesis May Be An Early Event In Crc Developmentmentioning
confidence: 96%